Tocilizumab in Uveitic Macular Edema Refractory to Previous Immunomodulatory Treatment. (4th March 2017) - Deuter, Christoph M. E.; Zierhut, Manfred; Igney-Oertel, Annette; Xenitidis, Theodoros; Feidt, Alexandra; Sobolewska, Bianka; Stuebiger, Nicole; Doycheva, Deshka
ABSTRACT: Purpose : To analyze the efficacy of tocilizumab in uveitic macular edema (ME) resistant to various immunomodulatory drugs. Methods : Patients received tocilizumab every 4 weeks intravenously. Central foveal thickness (CFT) was assessed by optical coherence tomography (OCT). Results : Five patients (8 eyes) who were ineffectively pretreated with systemic prednisolone, at least one immunosuppressive drug, and at least one biologic drug for uveitic macular edema were included in the study. At 3 months, a response of ME (≥25% reduction in CFT) was observed in 6 eyes (75.0%) of 5 patients. During follow-up, complete resolution of ME was achieved in 5 eyes (62.5%) of 4 patients. Improvement of BCVA was observed in 3 eyes of 3 patients, and stabilization in 3 eyes of 3 patients. Tocilizumab was well tolerated, and no severe side effects occurred. Conclusions : Treatment with tocilizumab can be considered in chronic uveitic macular edema even if previous immunomodulatory therapy has failed.